Health literacy and vaccination: A systematic review. Issue 2 (1st February 2018) - Lorini, Chiara; Santomauro, Francesca; Donzellini, Martina; Capecchi, Leonardo; Bechini, Angela; Boccalini, Sara; Bonanni, Paolo; Bonaccorsi, Guglielmo
ABSTRACT: This systematic review describes the current relationship between health literacy (HL) and vaccination (including attitude to vaccines, intention to vaccinate, and vaccine uptake). The aim is to comprehend the role of HL as a determinant of vaccine hesitancy. For this purpose, the following databases were explored from 1 January 2007 to 15 January 2017: PubMed, Embase, PsycINFO, ERIC, Health Evidence, Centre for Reviews and Dissemination, Scopus, Web of Science, and Cochrane Library . Nine studies were included in the final synthesis. The role of HL in predicting vaccine hesitancy or acceptance seems to be influenced by a few key factors. These include country, age, and type of vaccine. However, the relationship between HL and vaccination remains unclear. New research studies are needed—particularly longitudinal ones that use multiple measurement tools. This would facilitate a better understanding of the role of HL in predicting vaccine uptake.